The Relationship between Mobile Phone Anxiety and Sleep Quality Occupational Therapy in Adolescents and Its Internal Mechanism - Jingwen Bi (Hindawi-Wiley, 2022)
With the development of the Internet era, the application of smartphones in life is quite useful, and the penetration rate of smartphones will be further increased in the future, making teenagers increasingly dependent on mobile phones. Teenagers are under great academic pressure, and excessive reliance on mobile phones will inevitably affect the formation of normal values. Teenagers, as a special group, deserve our attention. Mobile phone dependence has become a social problem. In this paper, the Pittsburgh Sleep Quality Index was used to evaluate the sleep quality of adolescents, and the factors affecting the sleep quality of adolescents were explored from three dimensions of behaviour, physiology, and emotion based on the sleep quality model. In this study, structural equation modelling was used to test the multiple mediating effects and analyze the relationship between mobile phone anxiety and sleep quality. Through the analysis of the internal mechanism of the two, the results show that the average score of adolescents' anxiety about mobile phone use is 32.87, and the standard deviation is 10.67. The difference between mobile phone anxiety and sleep quality was statistically significant (P<0.001); good sleep quality can alleviate the prediction effect of mobile phone anxiety on anxiety and provide reference for promoting the physical and mental health development of adolescents.